EVALUATION OF THE INTERNAL CONTROL SYSTEM ON THE FUNCTION OF MEDICINE INVENTORY AT THE MOTHER AND CHILDREN'S HOSPITAL X IN MAKASSAR CITY - Wendy Kala Tikupadang (Entrepreneurship Undergraduate Program at Amkop Business School, 2023)
This research discusses the evaluation of the internal control system for the drug supply function at the X Mother and Child Hospital in Makassar City. The purpose of the research is to find out how the internal control system for the drug inventory function is carried out at RSIA X in Makassar City. This research uses descriptive analysis of the results of in-depth interviews with specified sources, field observations and documentation. The data used is in the form of primary data obtained from interviews and direct observation, secondary data obtained from documents related to drug supplies, acceptance documents, inventory cards, expenditure documents, and organizational structures. The results of this research indicate that RSIA X's internal control of drug supply has not been effective because there are still many things that must be added and reviewed by RSIA X, especially in ordering, receiving and storing medicines. Keywords: Internal Control System, Inventory